Intelligent Anticipatory Mobile Robot Networks for Autonomous Fruit Harvesting - Skulimowski, Andrzej M.J.; Karimi, Masoud (Wydawnictwo Politechniki Łódzkiej, 2023)
A relevant class of decision problems solved by autonomous robots consists in deriving consensus strategies for coordinated group task performance. This paper presents preference models for the above consensus problems termed anticipatory networks (AN). By definition, an AN is a multidigraph where temporally ordered agents are linked by a causal relation. Another partial order relation is anticipatory feedback which expresses preferences regarding some future decisions. We will present an application of the above model to coordinating fruit harvesting by autonomous robot teams. A graded freedom of the decision choice allows the robots to achieve desirable efficiency of the harvesting process.
Keywords: autonomous robots; intelligent decision agents; coordination; multicriteria decision theory; anticipatory networks; roboty autonomiczne; inteligentne czynniki decyzyjne; koordynacja; wielokryterialna teoria decyzji; sieci antycypacyjne